Robert Lafont, candidat des « minorités nationales » à l’élection présidentielle de 1974 - Damien Canavate (Lengas)
This article explores the disqualified candidacy of Occitan activist and intellectual Robert Lafont in the 1974 French presidential election within the broader context of regionalist claims in post-1968 France. This project united many left-wing regionalist groups fighting capitalism and advocating for regional autonomy, from Corsica to the Basque Country, Brittany, Northern Catalonia, and Occitania. Though brief, this event provoked significant political shifts within the Occitan movement. Soon thereafter, the Occitan support committees for Lafont's candidacy converted into a new autonomist and socialist organization: Volèm viure al païs.This article 1) highlights Robert Lafont's pivotal role in promoting regionalism in France during the 1960s and 1970s 2) assesses the political impact of the Occitan movement in the wake of 1968 and 3) shows how institutions filter electoral strategies at the fringes of mainstream politics.